Patterns of biologic and targeted-synthetic disease-modifying antirheumatic drug use in rheumatoid arthritis in Australia. (30th January 2022) - Fletcher, Ashley; Lassere, Marissa; March, Lyn; Hill, Catherine; Barrett, Claire; Carroll, Graeme; Buchbinder, Rachelle
Abstract: Objective: The aim of this study was to describe treatment patterns in RA, including the frequency and reasons for switching or stopping biologic and targeted synthetic DMARDs (b/tsDMARDs). Methods: The reasons for switching or stopping b/tsDMARDs were extracted from the Australian Rheumatology Association Database (ARAD) from 2003 to 2018 for RA participants. Switching patterns for each b/tsDMARD and time on first-, second- and third-line b/tsDMARDs were evaluated using Sankey diagrams and survival methods. Results: A total of 2839 participants were included in the analysis. The first-line b/tsDMARDs were etanercept ( n  = 1414), adalimumab ( n  = 1024), infliximab ( n  = 155), golimumab ( n  = 98), abatacept ( n  = 66), certolizumab ( n  = 38), tocilizumab ( n  = 21) and tofacitinib ( n  = 23). Of those starting first-, second- and third-line biologic therapy, 24.0%, 31.8% and 24.4% switched to another b/tsDMARD within 12 months, respectively. Inefficacy or adverse effects were the most common reasons for stopping therapy, irrespective of line of treatment. Compared with first-line etanercept, participants were more likely to stop adalimumab [Hazard ratio (HR) 1.16, 95% CI: 1.04, 1.29] and infliximab (HR 1.77, 95% CI: 1.46, 2.16). No differences were seen for other b/tsDMARDs. For second-line therapies compared with etanercept, the risk of stopping was lower for tocilizumab (HR 0.41, 95% CI: 0.25, 0.70), rituximab (HR 0.51, 95% CI: 0.30, 0.85) and tofacitinib (HR 0.29, 95% CI: 0.15, 0.57). Participants taking rituximab, tocilizumab and tofacitinib were also less likely to stop third-line therapy in comparison with participants taking etanercept. Conclusions: Switching between b/tsDMARDs was common among ARAD participants with RA, most commonly due to inefficacy or adverse effects. Durability of exposure and reasons for switching varied between b/tsDMARDs.